Intraocular pressure and choroidal thickness postural changes in multiple system atrophy and Parkinson’s disease - De Bernardo, Maddalena (Sci Rep, 2021)
To evaluate intraocular pressure (IOP) and choroidal thickness (ChT) postural changes in multiple system atrophy (MSA), Parkinson’s disease (PD) patients and healthy controls (HC). 20 MSA patients, 21 PD patients and 14 HC, were examined. All subjects underwent a complete examination, including corneal thickness, ChT, IOP and axial length (AL) measurements. IOP measurement was performed in supine, sitting, and standing positions, whereas ChT in sitting and standing positions. Supine to standing IOP variations were significantly higher in MSA vs PD(p = 0.01) and in MSA vs HC (p < 0.0001), whereas no significant differences were observed between PD and HC (p = 0.397). Mean sub-foveal ChT in MSA was 240 ± 92 μm in sitting position, and 215 ± 94 μm in standing position with a significant reduction (p = 0.008). Mean sub-foveal ChT in PD was 258 ± 79 μm in sitting position, and 259 ± 76 μm in standing position (p = 0.887). In HC it was 244 ± 36 μm in sitting position, and 256 ± 37 μm in standing position with a significant increase (p = 0.007). The significant IOP and ChT postural changes can be considered additional hallmarks of autonomic dysfunction in MSA and further studies are needed to consider them as biomarkers in the differential diagnosis with PD.